Regionalizações brasileiras: antigos legados e novos desafios - Rogério Haesbaert (Confins)
This article problematizes the Brazilian regionalization from issues coming from old regionalizations and the contemporary challenges to its realization. Both continuity and rupture tendencies are considered, both analytically and empirically. Some recent processes are pointed out, such as the Rio-São Paulo mega-region, the regions and/or regional networks in areas of agribusiness, the cross-border regions and, above all, ” regionalizations “from below”, produced through processes of resistance of subaltern groups.